Effects of jetstream on seasonal variations of tropical cyclone tracks in the East Sea - Vu Van, Thang; Bui Minh, Tuan; Tran Duy, Thuc; Cong, Thanh (Vietnam Journal of Earth Sciences, 2024)
Tropical cyclones (TCs) frequently occurs and result in substantial socio-economic consequences for the countries around the East Sea. In this study, the Joint Typhoon Warning Center (JTWC) best tracks and the NCEP/NCAR reanalysis data are employed to investigate the effect of jetstream on the seasonal variations of the TC tracks. The results reveal four primary directions of the tracks: northeastward, northwestward, westward and southwestward. A low-level anomalous cyclone moving from the Western North Pacific (WNP) to the Indochina Peninsula (IP) plays a significant role in guiding the movement of the TCs. This anomalous cyclone is strongly modulated by the development of a wavetrain along the subtropical jetstream. In May, the wavetrain induces strong anomalous divergence to the east of China, leading to the northeastward expansion of the low-level anomalous cyclones, thereby directing the TCs to the northeast. From June to August, the jetstream shifts to higher latitudes, reducing its impact on the TC tracks. From September to December, the jetstream moves back to the south; however, its effect on the TC tracks is opposite to that in May. During this time, the wavetrain accelerates an anomalous anticyclone in Southeast China and the Western North Pacific, which in turn pushes the anomalous cyclone to the south and promotes westward and southwestward movement of the TCs in the East Sea.